Pledgeted versus nonpledgeted sutures in aortic valve replacement: Insights from a prospective multicenter trialCentral MessagePerspective - Bart J.J. Velders, MD; Michiel D. Vriesendorp, MD; Joseph F. Sabik, III, MD; Francois Dagenais, MD; Louis Labrousse, MD; Vinayak Bapat, MD; Gabriel S. Aldea, MD; Anelechi C. Anyanwu, MD; Yaping Cai, MS; Robert J.M. Klautz, MD, PhD (JTCVS Techniques)
Objective: The objective of this study was to compare short- and midterm clinical and echocardiographic outcomes according to the use of pledgeted sutures during aortic valve replacement. Methods: Patients with aortic stenosis or regurgitation requiring aortic valve replacement were enrolled in a prospective cohort study to evaluate the safety of a new stented bioprosthesis. Outcomes were analyzed according to the use of pledgets (pledgeted group) or no pledgets (nonpledgeted group). The primary outcome was a composite of thromboembolism, endocarditis, and major paravalvular leak at 5 years of follow-up. Secondary outcomes included multiple clinical endpoints and hemodynamic outcomes. Propensity score matching was performed to adjust for prognostic factors, and subanalyses with small valve sizes (<23 mm) and suturing techniques were performed. Results: The pledgeted group comprised 640 patients (59%), and the nonpledgeted group 442 (41%), with baseline discrepancies in demographic characteristics, comorbidities, and stenosis severity. There were no differences between groups in any outcome. After propensity score matching, the primary outcome occurred in 41 (11.7%) patients in the pledgeted and 36 (9.8%) in the nonpledgeted group (P = .51). The effective orifice area was smaller in the pledgeted group (P = .045), whereas no difference was observed for the mean or peak pressure gradient. Separate subanalyses with small valve sizes and suturing techniques did not show relevant differences. Conclusions: In this large propensity score-matched cohort, comprehensive clinical outcomes were comparable between patients who underwent aortic valve replacement with pledgeted and nonpledgeted sutures up to 5 years of follow-up, but pledgets might lead to a slightly smaller effective orifice area in the long run.